Application of a Palm Oil-Based Alkyd for the Improvement of Polyaniline Properties. Issue 7 (September 2017) - Ramli, Mariam Fadzlina; Gan, Seng Neon; Lim, Wen Huei; Phang, Sook Wai
This study attempts to produce polyaniline (PAni)/Alkyd films with short curing time, good adhesion on fluoride-doped tin oxide (FTO) glass and having high conductivity that can be apply in solar cell panel. Both palm stearin-based alkyd resins and PAni were synthesized via chemical reactions. Chemical structures of the palm oil-based alkyd and PAni were investigated by proton nuclear magnetic resonance ( 1 H NMR), Fourier Transform Infrared (FTIR), and Ultraviolet-visible (UV-vis) spectrometers. Palm oil-based alkyds having three different acid number (AN) (5.66, 14.74, and 17.60 mg KOH/g) were blended with PAni at ratio of 1:0.5, 1:0.75, 1:1 for the preparation of PAni/Alkyd films via UV curing method. UV-vis spectrometer confirmed the chemical structure of PAni/Alkyd films. The adhesion of Pani/Alkyd films were tested following ASTM D3359 and conductivity study of PAni/Alkyd films was carried out using four point probe method. Best result was observed for PAni/ Alkyd at a ratio 1:0.5 with the palm oil-based alkyd having AN value of 5.56 mg KOH/g. The shortest curing time was 10 minutes, with strong adhesion of PAni/Alkyd films on FTO glass and conductivity of 2.5610 2 S/cm. By comparison the conductivity of the pure PAni was 1.31×10 3 S/cm.